2023
DOI: 10.1126/science.adf0895
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem-based management outperforms species-focused stocking for enhancing fish populations

Abstract: Ecosystem-based management is costly. Therefore, without rigorously showing that it can outperform traditional species-focused alternatives, its broad-scale adoption in conservation is unlikely. We present a large-scale replicated and controlled set of whole-lake experiments in fish conservation (20 lakes monitored over 6 years with more than 150,000 fish sampled) to examine the outcomes of ecosystem-based habitat enhancement (coarse woody habitat addition and shallow littoral zone creation) versus a widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…As an example, research on brown trout found long‐term supplementation significantly reduced genetic diversity among locations and compromised the conservation of local genetic variation (Fernández‐Cebrián et al, 2014), which threatened biodiversity in their southern range (Cagigas et al, 1999; Horreo et al, 2014; Splendiani et al, 2019). A tremendous amount of money and effort has been invested in restoring habitat to improve population productivity and increase carrying capacity (ISAB, 2015), and help offset future effects from climate change (Beechie et al, 2013; Bilby et al, 2022), an action demonstrated to increase wild fish abundance more effectively than species‐specific stocking efforts (Radinger et al, 2023). Because the resilience of salmonids also depends on their functional genetic capacity to survive and reproduce in a changing environment (Kardos et al, 2021), future research could help illuminate the extent to which, if any, alterations to genetic diversity may influence returns on habitat investments where both hatchery and wild fish co‐exist.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, research on brown trout found long‐term supplementation significantly reduced genetic diversity among locations and compromised the conservation of local genetic variation (Fernández‐Cebrián et al, 2014), which threatened biodiversity in their southern range (Cagigas et al, 1999; Horreo et al, 2014; Splendiani et al, 2019). A tremendous amount of money and effort has been invested in restoring habitat to improve population productivity and increase carrying capacity (ISAB, 2015), and help offset future effects from climate change (Beechie et al, 2013; Bilby et al, 2022), an action demonstrated to increase wild fish abundance more effectively than species‐specific stocking efforts (Radinger et al, 2023). Because the resilience of salmonids also depends on their functional genetic capacity to survive and reproduce in a changing environment (Kardos et al, 2021), future research could help illuminate the extent to which, if any, alterations to genetic diversity may influence returns on habitat investments where both hatchery and wild fish co‐exist.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Ecosystem-based management has been proven to be superior to other measures. 77 While our results are the result of observational studies and do not imply direct causality, the identified patterns are plausible from a mechanistic perspective and suggest predominant importance for understanding the relationships between the decline of community stability and environmental stressors, at least for the data observed in the Shaying River. The large spatial extent and high realism of the assessed parameters contribute to the relevancy.…”
Section: Discussionmentioning
confidence: 60%
“…In general, on the basis of 3 years of eDNA data sets, our study revealed potential mechanisms of destabilizing effects of aquatic multiple communities across a major river basin under persistent stressors and found that the decline of community stability mainly depended upon the diversity-mediated pathway, including the increase of species synchrony and the changes of interaction networks. These findings have certain implications for the development of “alert indicators” based on community stability to identify the potential effect thresholds of environmental stressors from the management perspectives, because stability metrics (including species stability and network stability) have strong linkages with ecosystem services and functions. , Ecosystem-based management has been proven to be superior to other measures …”
Section: Discussionmentioning
confidence: 99%
“…As a result of increased industrialization and overpopulation, the quantity of toxic metals in the environment is increasing, including the air, soil, water, and food 13 . In the wildlife species‐focused stocking for enhancing fish populations should be replaced by eco‐system‐based management 14 . Thus, the low‐specific population sizes necessitate urgent international conservation efforts, prevention of extinction, and species reintroduction 15…”
Section: Relevance Of the One Health Approach For Clinical Practice A...mentioning
confidence: 99%